PERANCANGAN STRATEGI VISUAL DIGITAL MARKETING MADRASAH IBTIDAIYAH (MI) BAITUL AMAR UNTUK ORANGTU - Wahyu Amarulloh Pulungan; Widiya Lestari Harahap (JURNAL RUPA MATRA, 2023)
Madrasah Ibtidaiyah (MI) Baitul Amar has been established for 10 years and has produced many graduates who become tahfidz Al-Qur'an. Not only that, Madrasah Ibtidaiyah (MI) Baitul Amar has won various achievements in various fields, both from the sub-district to the national level. Even so, the number of students at Madrasah Ibtidaiyah (MI) Baitul Amar tends to be small when compared to competitors, this is due to a lack of marketing strategy so that Madrasah Ibtidaiyah (MI) Baitul Amar is not widely known. Madrasah Ibtidaiyah (MI) Baitul Amar still relies on traditional marketing media to promote its business, and has never put any effort into promoting it through online media. Therefore the author carried out this design as an effort to build a brand image and bring in new prospective students for the Madrasah Ibtidaiyah (MI) Baitul Amar.